Methods of grain storage in Jabalpur region - Gupta, A K; Waghmare, Deepika; Bhalavi , Sangeeta; Marskole , Twinkle; Maravi , Sanjan (Journal of Postharvest Technology, 2016)
A survey was conducted in Panagar, Mahrajpur, Lakhadon and Bargaht villages of Jabalpur to find out the storage practices prevalent in the  adjoining area. Information regarding the nature and capacity of the storage structure, material used for construction and the extent of losses  to crops stored was collected. Kothi, Bunda, Mandulia, Jute and Polypropylene bags are commonly used for grain storage. An average loss of  2% occurs during the storage period. Jute and Polypropylene bags are gaining popularity as these are light in weight and easy in handling.
Keywords: Bunda; Jute; Kothi,; Polypropylene bags,; cereal storage